Pengaruh Pembelajaran Kewirausahaan dan Latar Belakang Orang Tua Terhadap Motivasi Berwirausaha Siswa Kelas XI SMKN Kota Malang - Savitri, Silvi Diah; Sunarni, Sunarni; Sobri, Ahmad Yusuf (Universitas Negeri Malang, 2024)
Abstract: This study aims to determine: (1) the influence of parents' background on entrepreneurial motivation among students of Grade XI in state vocational schools in Malang City; (2) the influence of entrepreneurship education on entrepreneurial motivation among students of Grade XI in state vocational schools in Malang City; and (3) the influence of parents' background and entrepreneurship education on entrepreneurial motivation among students of Grade XI in state vocational schools in Malang City. This research adopts a quantitative approach with descriptive analysis and regression analysis to examine the relationships between variables. The results of this research indicate that: (1) there is a simultaneous influence of parents' background and entrepreneurship education on entrepreneurial motivation among students of Grade XI in state vocational schools in Malang City; (2) there is no significant influence of parents' background on entrepreneurial motivation among students of Grade XI in state vocational schools in Malang City; and (3) there is a significant influence of entrepreneurship education on entrepreneurial motivation among students of Grade XI in state vocational schools in Malang City.Keywords: Parents' Background, Entrepreneurship Education, Entrepreneurial Motivation. Abstrak: Penelitian ini bertujuan untuk mengetahui: (1) adanya pengaruh latar belakang orang tua terhadap motivasi berwirausaha peserta didik kelas XI SMK Negeri di Kota Malang; (2) adanya pengaruh pembelajaran kewirausahaan terhadap motivasi berwirausaha peserta didik kelas XI SMK Negeri di Kota Malang; dan (3) adanya pengaruh latar belakang orang tua dan pembelajaran kewirausahaan terhadap motivasi berwirausaha peserta didik kelas XI SMK Negeri di Kota Malang. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis deskriptif dan analisis regresi untuk mengetahui pengaruh antar variabel. Hasil penelitian ini menunjukkan: (1) adanya pengaruh simultan antara latar belakang orang tua dan pembelajaran kewirausahaan terhadap motivasi berwirausaha peserta didik kelas XI SMK Negeri di Kota Malang; (2) tidak terdapat pengaruh yang signifikan variabel latar belakang orang tua terhadap motivasi berwirausaha peserta didik kelas XI SMK Negeri di Kota Malang; dan (3) adanya pengaruh yang signifikan antara pembelajaran kewirausahaan terhadap motivasi berwirausaha peserta didik kelas XI SMK Negeri di Kota Malang.Kata kunci: Latar Belakang Orang Tua, Pembelajaran Kewirausahaan, Motivasi Berwirausaha